Comparative Analysis of Peri-Implant Bone Loss in Extra-Short, Short, and Conventional Implants. A 3-Year Retrospective Study - Estévez Pérez, Daycelí; Bustamante Hernández, Naia; Labaig Rueda, Carlos; Solá Ruíz, María Fernanda; Amengual Lorenzo, José; García-Sala Bonmatí, Fernando; Zubizarreta Macho, Álvaro; Agustín Panadero, Rubén (My University, 2021)
Objective: To evaluate the influence of implant length on marginal bone loss, comparing implants of 4 mm, 6 mm, and >8 mm, supporting two splinted crowns after 36-month functional loading. Materials and Methods: this retrospective clinical trial evaluated the peri-implant behavior of splinted crowns (two per case) on pairs of implants of the same length placed in the posterior maxilla (molar area). Implants were divided into three groups according to length (Group 1: extrashort 4 mm; Group 2: short 6 mm; Group 3: conventional length >8 mm). Marginal bone loss was analyzed using standardized periapical radiographs at the time of loading and 36 months later. Results: 24 patients (19 women and 5 men) were divided into three groups, eight rehabilitations per group, in the position of the maxillary first and second molars. The 48 Straumann® Standard Plus (Regular Neck (RN)/Wide Neck (WN)) implants were examined after 36 months of functional loading. Statistical analysis found no significant differences in bone loss between the three groups (p = 0.421). No implant suffered biological complications or implant loss. Long implants were associated with less radiographic bone loss. Conclusions: extra-short (4 mm); short (6 mm); and conventional length (>8 mm) implants in the posterior maxilla present similar peri-implant bone loss and 100% survival rates in rehabilitation, by means of two splinted crowns after 36 months of functional loading. Implants placed in posterior positions present better bone loss results than implants placed in anterior positions, regardless of the interproximal area where bone loss is measured. Conventional length (>8 mm) implants show better behavior in terms of distal bone loss than short (6 mm) and extra-short (4 mm) implants.